The center and the Lie structure of a Leavitt path algebra - Siles-Molina, Mercedes (My University, 2017)
Este es el curso que impartí en la Escuela de investigación "CIMPA School Recent trends in non-commutative algebra" en junio de 2017 en Pune, India (véase https://iiserpunecimpa17.wordpress.com/)
Keywords: Lie, Algebras de; Leavitt path algebra; Center; Undecomposable algebra; Lie algebra